Studying Hinduism: key concepts and methods - Mittal, Sushil; Thursby, Gene R. (Routledge, 2008)
This book is an indispensable resource for students and researchers wishing to develop a deeper understanding of one of the world's oldest and most multifaceted religious traditions. Sushil Mittal and Gene Thursby, leading scholars in the field, have brought together a rich variety of perspectives which reflect the current lively state of the field. "Studying Hinduism" is the result of cooperative work by accomplished specialists in several fields that include anthropology, art, comparative literature, history, philosophy, religious studies, and sociology. Through these complementary and exciting approaches, students will gain a greater understanding of India's culture and traditions, to which Hinduism is integral. The book uses key critical terms and topics as points of entry into the subject, revealing that although Hinduism can be interpreted in sharply contrasting ways and set in widely varying contexts, it is endlessly fascinating and intriguing.